Numerical optimization of unsteady natural convection heat transfer from a pair of horizontal cylinders - MURRAY, DARINA; PERSOONS, TIM (My University, 2016)
This paper presents the results of a numerical study of unsteady natural convection heat transfer from a pair of isothermally heated horizontal cylinders in water. In conjunction with the developed numerical model, a genetic algorithm is designed to search for the optimal spacing between the two cylinders that maximizes their overall heat transfer. When the cylinders are vertically aligned, the heat transfer effectiveness of the upper cylinder is affected by buoyancy-induced fluid flow induced by the lower cylinder. The established and validated CFD model is used to analyse spectral data of local Nusselt number and velocity. The optimization procedure identifies the optimal spacing for Rayleigh numbers ranging from 1e+6 to 1e+7.
Journal of Physics: Conference Series
7th European Thermal Sciences Conference
PUBLISHED
Krakow, Poland
Keywords: numerical study of unsteady natural convection heat transfer; numerical study of unsteady natural convection heat transfer; Smart & Sustainable Planet